Application of Project-Based Learning Through a STEM Approach to Improve Learning Outcomes During a Pandemic - Yoana Nurul Asri; Desta Sulaesih Mursyidah; Vini Rizqi (Postgraduate, University of Mataram, 2021)
Research has been conducted on applying project-based learning (PjBL) through the Science, Technology, Engineering, and Mathematics (STEM) approach during the pandemic. Tests were given to 30 first-year students conducted by Distance Learning (DL). The research method used a pre-post experimental one-group design. The results showed a minimum pretest score of 50 and a maximum value of 70. After being treated, the minimum posttest result was 75, and the maximum result was 90. There was a significant difference of 60 for the average pretest and posttest from the average pretest and posttest. The average posttest is 79.